The influence of blended learning activities in academic performace in the learning of english as a foreign language, language department, University of Cuenca - Espinoza Hidrobo, María Isabel
Due to the fact that today?s educational trends and approaches have a lot to do with technology and online resources and because of limited access to school computer labs, this research has been done. This thesis emphasizes the importance of teachers applying constructivism in their courses through the use of a wide range of online options that this globalized world offers such as Moodle and web tools combined with face-to-face sessions. For that purpose, a comparison of academic performance has been made in order to compare students? outcomes and achievement, first in a face-to-face class, and then with a focus group which worked with a blended learning approach through the platform of the University of Cuenca as a means to develop the activities. Even though the students? performance in the end was not as expected, many significant findings are explained throughout this work. As a conclusion, this work suggests the adoption and implementation of blended courses, so the students can get the most from both face-to-face and blended learning approaches.